REMOTE RESULTS OF SURGICAL TREATMENT OF PATIENTS WITH PROXIMAL HUMERAL FRACTURES - Мihail Gasko; Petro Kovalchuk; Serhiy Tulyulyuk; Svitlana Namestiuk (World Science, 2021)
Proximal humeral fractures constitute 5-8% of all the fractures of the limbs and 80% of fractures of the upper arm. To report about remote results of the suggested tactics of surgical treatment of proximal humeral fractures. Satisfactory results of treatment were found in 21 (80,7%) patients out of 26 (72%), who underwent closed reduction of fractures with pin fixation. This group of patients achieved consolidation in optimal terms, and the function of the shoulder joint was satisfactory with abduction angle of 90°. 2 (7,7%) patients experienced secondary dislocation of fragments and their QuickDASH score was 38.4. 3 (11,6%) patients achieved consolidation of fracture, but stable contracture of the shoulder joint occurred. Their QuickDASH score was 38.4. Osteosynthesis with plates was performed in 10 patients. 3 (30%) of them developed aseptic necrosis of the humeral bone head, 2 (20%) patients developed suppuration of the soft tissues which produced a negative effect of the patients’ ability to work ‒ QuickDASH score 42,7, 5 (50%) patients admitted satisfactory results of treatment ‒ QuickDASH score 21,5. Osteosynthesis with plates was performed in 10 patients. 3 (30%) of them developed aseptic necrosis of the humeral bone head, 2 (20%) patients developed suppuration of the soft tissues which produced a negative effect of the patients’ ability to work ‒ QuickDASH score 42,7, 5 (50%) patients admitted satisfactory results of treatment ‒ QuickDASH score 21,5. The tactics of surgical treatment of patients with proximal humeral fractures depends on the following: type of a fracture, patient’s age, concomitant pathology and osteoporosis available, and patient’s social needs.